2016
DOI: 10.3389/fdigh.2016.00005
|View full text |Cite
|
Sign up to set email alerts
|

The Distance between Us: Using Construal Level Theory to Understand Interpersonal Distance in a Digital Age

Abstract: Several authors have shown how communication using digital devices influences the experience of psychological distance. For instance, the hyperaccessibility associated with mobile phones reduces the felt distance between people who are separated by geographical space (Cummings et al., 2001;Sommer, 2002;Turkle, 2006;Katz and Byrne, 2013). This paper discusses how interpersonal distance, i.e., the perception of separation in space and time that people sense between themselves and others who are significant to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 10 publications
0
21
0
Order By: Relevance
“…Online platforms provide opportunities to meet and discuss without being physically close to each other. However, this type of technology may not reproduce the same interpersonal distance as physical presence [ 16 ]. Students may feel distant and detached from the rest of the group despite being connected via the computer screen and audio.…”
Section: Discussionmentioning
confidence: 99%
“…Online platforms provide opportunities to meet and discuss without being physically close to each other. However, this type of technology may not reproduce the same interpersonal distance as physical presence [ 16 ]. Students may feel distant and detached from the rest of the group despite being connected via the computer screen and audio.…”
Section: Discussionmentioning
confidence: 99%
“…First, whereas previous research showed the effects of psychological distance in offline contexts [16,26,28], this has not been fully investigated in relation to Web-based communication contexts. It has been suggested that Web-based environments permit more confounded relationships for psychological distance dimensions (eg, with videoconferencing one can interact with spatially distant others in real time) compared with offline contexts [36]. Whether spatial distance is still important in Web-based contexts is a debated topic [37-39].…”
Section: Discussionmentioning
confidence: 99%
“…When exercising at home, one needs to adhere to the following rules [7,8]: 1. Workouts should be done in a room or outdoors; 2.…”
Section: Resultsmentioning
confidence: 99%